Analysis on related risk factors for cardiocerebral vascular diseases in patients with diabetic kidney disease - ZHANG Zhi-xu; GAO Ai-qing; RAO Xiao-pang (Linchuang shenzangbing zazhi)
Objective To investigate the epidemiology and related risk factors for cardiocerebral vascular diseases in patients with diabetic kidney diseases（DKD）.Methods A total of 800 patients with DKD hospitalized in Chengyang District People’s Hospital of Qingdao from January 2016 to December 2017 were enrolled in this study.Based on complications of cardiocerebral vascular diseases, the patients were divided into the cardiocerebral vascular disease group（n=558） and group without cardiocerebral vascular diseases（n=242）.The general information,including gender,age,body mass,height,systolic blood pressure（SBP）, diastolic blood pressure（DBP）,drinking history and smoking history, and laboratory test indicators, including fasting blood glucose（FBG）, glycosylated hemoglobin（HbA1 C）, liver and kidney functions, total cholesterol（TCH）, triglyceride（TG）, low density lipoprotein cholesterol（LDL-C）, high density lipoprotein cholesterol（HDL-C）, Lipoprotein A（Apoa）,parathyroid hormone（PTH）, C-reactive protein（CRP）, hemoglobin（Hb）, white blood cells（WBC）, brain natriuretic peptide（BNP）, urinary microalbumin/urinary creatinine ratio（UACR） and serum β2-microglobulin（β2-MG）were detected. Multivariate Logistic regression analysis was used to analyze the risk factors in diabetic kidney disease patients with cardiocerebral vascular diseases.Results Among the 800 patients with diabetic kidney disease,558 ones had cardiocerebral vascular complications（69.75%）, with the incidences of coronary artery disease（CAD）,left ventricular hypertrophy（LVH）,congestive heart failure（CHF）,cerebral vascular accident（CVA）and large atherosclerosis（LA）of 12.50%（100/800）, 4.13%（33/800）, 4.37%（35/800）, 13.75%（110/800）and,35.00%（280/256）,respectively.The incidences of the above five cardiocerebral vascular complications of DKD patients with chronic kidney disease（CKD） stage I to V were 2.50%（20/800）, 3.75%（30/800）, 12.50%（100/800）, 17.5%（140/800） and 33.5%（268/800）, respectively.The differences of the incidences of the above five cardiocerebral vascular complications between DKD patients with difference CKD stages had statistical significance（χ2=14.138,P=0.001）.There were differences of statistical significance（P<0. 05） of age, body mass index（BMI）, SBP, drinking rate, smoking rate, HbA1 C, Scr, SUA, TC, LDL-C, UACR, Apoa, PTH and β2-MG between the two groups. Multivariate Logistic regression analysis showed that age,SUA,Apoa, LDL-C,UACR and serum β2-MG levels were independent influence factors for cardiocerebral vascular complications in diabetic kidney disease patients（P<0.05）.Conclusions Cardiocerebral vascular complications are prone to detect in DKD patients, Age, SUA, Apoa, LDL-C, UACR and β2-MG levels influence incidences of cardiocerebral vascular complications in DKD patients.